Polyfunctional radiosensitizers IV. The effect of contact time and temperature on sensitization of hypoxic Chinese hamster cells in vitro by bifunctional nitroxyl compounds. - Millar, B. C. (Nature Publishing Group, 1978)
Three biradical nitroxyl compounds have been shown to modify the slope and shoulder region of the hypoxic cell survival curve of V79 cells to different degrees. The amount of sensitization produced by these compounds is dependent on the cell-drug contact time at both 20 degree and 37 degree C whereas sensitization by the monoradical nitroxyl, NPPN, is independent of these factors. The results suggest that biradicals may modify cellular biochemistry in such a way as to change the repair capacity of the cells. This could be responsible for changes in the shape of survival curves when cell-drug contact times are increased.